Argentina: Feeding on Food Crisis? - Ozyigit, Ahmet; Eminer, Fehiman (Journal of Asian Business Strategy, 2011)
This article uses a Vector Error Correction Model (VECM) framework to estimate simultaneously the short-run and long-run relationship between food price inflation and poverty reduction in Argentina. Results from the cointegration tests reveal that economic growth, food price inflation and poverty reduction exhibit a long-run relationship. The results from the VECM support the argument that there exists a uni-directional causality running from food price inflation and economic growth to poverty reduction, but not the other way around. Argentina has, in fact, witnessed substantial poverty reduction as a response to the global food crisis by maintaining its position as a net exporter of food products.